Potential of Implementing the Low Concentration Photovoltaic Systems in the United Kingdom - Siti Hawa Abu-Bakar; Firdaus Muhammad-Sukki; Daria Freier; Roberto Ramirez-Iniguez; Tapas Kumar Mallick; Abu Bakar Munir; Siti Hajar Mohd Yasin; Abdullahi Abubakar Mas’ud; Siti Sarah Abu-Bakar; Nurul Aini Bani; Mohd Nabil Muhtazaruddin (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper discusses the prospect of integrating a novel type of low concentration photovoltaic (LCPV) design known as the rotationally asymmetrical compound parabolic concentrator (RACPC) in a building in the United Kingdom. This is done by proposing a number of building integration designs to create a zero carbon building. A cost reduction analysis of installing the LCPV systems in the country is also presented. It was found that an RACPC design could reduce the LCPV module’s manufacturing cost by 31.75% and the LCPV module’s cost per unit power output by 33.87% when compared with the conventional PV module.